642 Potential Protective Effects of Trigonella Foenum Graecum and Sodium Orthovanadate in Hyperglycemia-Induced Alterations in Cardiac Membrane in Alloxan Diabetic Rats. (October 2012) - Kumar, P; Kale, RK; Baquer, NZ
Abstract : Objectives: Oxidative stress in diabetic tissues is accompanied by high level of free radicals and the simultaneously declined antioxidant enzymes status leading to cell membrane damage. In the present study, the effect of sodium orthovanadate (SOV) and Trigonella foenum graecum seed powder administration has been studied on blood glucose and insulin levels, membrane bound ATPases (Na+K+ATPase, Ca 2 +ATPase), antioxidant enzymes (superoxide dismutase, glutathione S-transferases), lipid peroxidation, lipofuscin accumulations and distribution of glucose transporter (GLUT4) in heart of the alloxan induced diabetic rats and to see whether the treatment with SOV and Trigonella is capable of reversing these effects. Methods: Diabetes was induced by administration of alloxan monohydrate (15mg/100g b.wt.) and female rats were treated with 2IU insulin, 0.6mg/ml SOV, 5% Trigonella in the diet and a combination of 0.2mg/ml SOV with 5% Trigonella separately for 21 days. Results: Diabetic rats showed hyperglycemia with almost four fold high blood glucose levels. Hyperglycemia increases lipid peroxidation and lipofuscin accumulations, causing decreased activities of membrane bound ATPases, antioxidant enzymes and GLUT4 expression with diabetes in the rat heart. Rats treated with combined dose of vanadate and Trigonella had glucose levels comparable to controls, similar results were obtained with the activities of antioxidant enzymes, membrane bound ATPases, lipofuscin, lipid peroxidation and GLUT4 in diabetic rats. Conclusion: Our results showed that lower doses of vanadate (0.2mg/ml) could be used in combination with Trigonella to effectively counter diabetic alterations without any toxic side effects.